Unveiling the relationship between language learning beliefs, emotions, and identities - Barcelos, Ana Maria Ferreira (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2015)
Several authors (Frijda, Manstead, & Bem, 2000; Van Veen & Lasky, 2006) suggest that emotions, cognitions, and identities are intrinsically related. Authors in social psychology (Fiedler & Bless, 2000; Frijda, Manstead, & Bem, 2000; Rosiek, 2003) have considered how beliefs are particularly sensitive to affective influences and how emotions, cognitions, and identities are intrinsically related. Understanding this relationship would help researchers to reveal complex key issues in beliefs research, such as the relationship between beliefs and action. Yet, although research on beliefs in applied linguistics goes back to the 70s and 80s, there has been scant connection with emotions and identities. This paper aims to reflect on the relationship between beliefs, emotions, and identities by looking at these coconstructing, overlapping concepts to advance our understanding of language learning and teaching. Through a review of studies on beliefs, emotions, and identities within applied linguistics and other areas, I illustrate how beliefs and emotions are intrinsically and interactively related, and how beliefs within a socio-historical context influence the construction of identities. Identities influence the kinds of emotions and beliefs that individuals attribute to themselves and to others. Emotions, in turn, can influence identities and how we construct them. Implications for research on beliefs, emotions, and identities are suggested.
Keywords: emotions; identities; beliefs; language teacher education; language learning